The Determinants of Corporate Research and Development Expenditure in UK - He, Peixuan (2009)
This dissertation examined determinants of Research and Development among UK public listed companies. The main variable under investigation is typically Schumpeterian variables. Additionally, internal finance related variables, human capital accumulation and competition variables are estimated in the model developed from Howe and McFetridge. A comparison of the determinants between high technology firms and relatively low technology firms is done to address certain degree of industrial characteristics. After taking serial correlation and correlated heterogeneity and explanatory variables, the following results emerge. Generally speaking, there is a inverted U-shape relationship between firm size and R&D expenditure. Previous net profit and the foreign ownership promote corporate spending on R&D activities. Free cash flow negatively associated with R&D expenditure. However, when granting detailed insight into two subdivide samples, the inverted U-shape firm size and R&D spending relationship still holds. Foreign ownership becomes insignificant. On the other side, large firms still spend more in R&D behavior in low-tech firms but the U-shape relationship disappears. Capital structure appears as an important determinant for the low technology firms.